Dinamika Politik Islam Semenanjung Arab 1800-1930 M dan Pengaruh Berdirinya Kerajaan Arab Saudi Modern terhadap Praktik Keagamaan - Agustono, Ihwan (MarÃƒÂ¢ji`: Jurnal Ilmu Keislaman, 2016)
The article examines the dynamics of political Islam of the Arabian Peninsula in 1800-1930 and their influence to the foundation of the Modern Saudi Arabia Kingdom and their impact to religious practices in the Holy Land. The study is considered important due to the changing phenomenon of religious under-standing in the Holy Land. A new orthodox ideology has been able to change the well-established traditional understanding and become a dominant school until nowadays. The study concludes that: 1) Socio-political constellation of Hijaz before 19th century had been marked by the decrease of political supremacy of Hijaz along with far migration of the Islamic governmental center from Madinah; 2) One of the culminations of political dynamics of the Arabian Peninsula between 1800 and 1930 was the establishment of the Modern Saudi Arabia Kingdom; 3) Such political dynamics have subsequently resulted in the purification of Islamic sharÃ®âah in accordance with the Wahabiâs doctrines, obliteration of the tradition of four maqÃ¢mÃ¢t in Masjid al-H{arÃ¢m, conformation of Islamic education with the Wahabiâs dogmas, and the increase of orthodoxy and the decrease of popular Sufiâs credo.